A critical review of physical activity figures for comparison studies using IPAQ surveys and accelerometer measurements - Bergier, Józef (Journal of Health Inequalities, 2017)
Determining physical activity requires the use of such widely recognised assessment methods as the International Physical Activity Questionnaire (IPAQ) and accelerometers. This study reviews national and international research that used these tools in the years 2007-2016 for assessing physical activity in school children. Our analysis discovered higher levels of self-reported physical activity when the IPAQ version with the longer questionnaire was employed. The metabolic equivalent task (MET)-minutes/week figures, obtained from the long and short questionnaire versions, showed very large disparities, which should in future serve as a signalling mechanism, so that researchers have a better understanding of how this assessment instrument is to be used. In the author’s opinion, physical activity in young people will be assessed more objectively when both these tools are employed simultaneously.